Improvement of German Simple Text Writing Skills Through Stationlernen Learning Method - Clarissa Anggita Karangan; Syamsurijal Syamsurijal (Universitas Negeri Makassar, 2025)
Abstract. This research aims to improve the German simple text writing skills of XII grade students of SMA Negeri 14 Makassar by using the Stationlernen learning method. This research is a class action research (PTK) which includes planning, implementation, observation, and reflection. The subjects of this study were XII IPS 2 class students totaling 29 people. In this research, there are two types of data, namely qualitative data which describes the results of implementation and observation during learning, as well as quantitative data which is the result of the test of students' German simple text writing skills in cycle I and cycle II. The results of the students' German simple essay writing test in cycle I obtained an average of 63.79 and increased in cycle II with an average value of 80.27. The results of this research indicate that the application of the Stationlernen learning method can improve students' German simple text writing skills.Keyword: Learning Methods, Simple Text , Writing Skills, Stationlernen